Behavior of Ompok hypophthalmus reared under different photoperiod - Rahmat Syafri; Deni Efizon; Windarti ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Fish behavior is affected by environmental condition, including photoperiod. Tounderstand the effects of different photoperiod toward O. hypophthalmus behavior, astudy has been conducted in Oktober 2015. The fish was reared in fiber tanks size100cm X 50cm dan height 40cm with water circulation system. The tanks were placedunder plastic tents that were completed with light bulb and timer to adjust the time.There were 5 treatments applied, namely Control (natural photoperiod), 24 hours dark(24D), 16 dark and 8 hours light (16D8L), 8 dark and 16 hours light (8D16L) and 24hours light (24L). Fish behavior was monitored hourly for a 72 hours periodcontinuously. Swimming and schooling activities, fish position and respons to light andfood were noted. Results shown that the photoperiod clearly affects the behavior offish. During the dark, fish tend to be in the surface, swimming actively, do not form agroup, sensitive to light and very agresive to take food provided. In contrast, during thelight period, fish less active, tend to form a group in the bottom of the tank, lesssensitive to light and less aggresive in taking food. Based on data obtained, it can beconcluded that photoperiod is affect the behavior of fish in general.Keywords: photoperiod, Ompok hypophthalmus, Behavior, Dark, Light